Safety and efficacy of tirofiban after early neurological deterioration in patients with branch atheromatous disease receiving alteplase - Zhong, Xuemin; Zhao, Meng; Xu, Ronghua; Wang, Jian; Du, Jiaxiu (Frontiers in Stroke, 2022)
Background: We evaluated the safety and effectiveness of administering tirofiban after the occurrence of early neurological deterioration (END) in patients with branch atheromatous disease (BAD) receiving alteplase Methods: Bleeding incidence, National Institute of Health Stroke Scale (NIHSS) score, and modified Rankin scale (mRS) score were assessed in 193 patients with BAD receiving intravenous alteplase within 4.5 hours of stroke onset. Results: Among 193 patients, 119 did not experience exacerbation after thrombolytic treatment, 74 (38.34%) had END, 34 were treated with tirofiban after END, and 40 received standard medical treatment. On the seventh day or at discharge, no cases of symptomatic cerebral hemorrhage were noted in any group, and no patient died during the 90-day follow-up period. There were five, three, and two cases of gastrointestinal bleeding without aggravation after thrombolytic therapy, without tirofiban after thrombolytic therapy, and with tirofiban therapy, respectively, and all were positive on fecal occult blood test. Furthermore, 52 of 74 patients (70.27%) had a good mRS score at 90 days. Among patients with END after thrombolytic therapy who received tirofiban, 27 (79.41%) had a good mRS score at 90 days, which was significantly better than that of 18 cases that did not receive tirofiban after exacerbation (45%) (P<0.001).NIHSS scores at 24 hours, 48 hours and 7 days after tirofiban treatment in patients with exacerbation after thrombolytic therapy were significantly lower than that without tirofiban. Conclusions: Patients with BAD have elevated risks of END after thrombolytic therapy. Compared with conventional oral antiplatelet aggregation drugs, tirofiban rescue therapy resulted in significantly better NIHSS and mRS scores without increased bleeding rates.